2015
DOI: 10.3758/s13414-014-0829-6
|View full text |Cite
|
Sign up to set email alerts
|

Tactile search for change has less memory than visual search for change

Abstract: Haptic perception of a 2D image is thought to make heavy demands on working memory. During active exploration, humans need to store the latest local sensory information and integrate it with kinesthetic information from hand and finger locations in order to generate a coherent perception. This tactile integration has not been studied as extensively as visual shape integration. In the current study, we compared working-memory capacity for tactile exploration to that of visual exploration as measured in change-d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
13
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 36 publications
0
13
0
Order By: Relevance
“…Experiments that have demonstrated change blindness in touch (e.g., Yoshida et al, 2015) have typically removed any possibility of participants identifying the tangible stimuli. Their research paradigms used line orientation or spatial position as the change with simple straight, line-shaped vibrotactile configurations.…”
Section: Experiments 5: Shape Versus Orientation Change With Lettersmentioning
confidence: 99%
See 3 more Smart Citations
“…Experiments that have demonstrated change blindness in touch (e.g., Yoshida et al, 2015) have typically removed any possibility of participants identifying the tangible stimuli. Their research paradigms used line orientation or spatial position as the change with simple straight, line-shaped vibrotactile configurations.…”
Section: Experiments 5: Shape Versus Orientation Change With Lettersmentioning
confidence: 99%
“…Consequently, Experiment 6 provided a direct comparison of a haptic letter exchange position group with one in which new letters were substituted for old ones in the change task. This experiment was also intended to further test the extreme idea that when using touch, one has little or no understanding of the spatial relations in a complex display (e.g., Yoshida et al, 2015). It is important that this earlier report by Yoshida et al used patterns that were all identical, namely vibrotactile lines that varied in location or orientation.…”
Section: Experiments 6: Letter Exchange Compared With Changes Involving New Lettersmentioning
confidence: 99%
See 2 more Smart Citations
“…Mueller et al showed that occupation-related long-term sensory training enhances roughness discrimination 14 . Conversely, recent data shows that the tactile search for changes involves less memory than visual search for changes, because the working memory has higher availability for the visual system and the haptic perception has a poorer working memory capacity 15 .…”
mentioning
confidence: 99%